Living with Uncertainty: The Moral Significance of Ignorance - Zimmerman, Michael J (Cambridge University Press, 2013)
Every choice we make is set against a background of massive ignorance about our past, our future, our circumstances, and ourselves. Philosophers are divided on the moral significance of such ignorance. Some say that it has a direct impact on how we ought to behave – the question of what our moral obligations are; others deny this, claiming that it only affects how we ought to be judged in light of the behavior in which we choose to engage – the question of what responsibility we bear for our choices. Michael Zimmerman claims that our ignorance has an important bearing on both questions, and offers an account of moral obligation and moral responsibility that is sharply at odds with the prevailing wisdom. His book will be of interest to a wide range of readers in ethics.